2000
DOI: 10.1046/j.1365-2672.2000.00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Vibrio cholerae virulence genes among different Vibrio species isolated in Sardinia, Italy

Abstract: The members of the genus Vibrio include harmless aquatic strains as well as strains capable of causing epidemics of cholera. Diarrhoea caused by Vibrio cholerae is attributed to cholerae enterotoxin (CT) codified by the ctx operon and regulated by a number of virulence genes such as toxT, toxR and toxS. Fifty-two Vibrio strains were isolated from different aquatic environments in and around Sardinia and searched by PCR for the presence of ctxA, zot, ace, toxR, toxS, toxT, tcpA and vpi virulence genes in the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
63
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 20 publications
7
63
0
1
Order By: Relevance
“…The plasmids were transformed into E. coli JM109 competent cells, and the sequence of the cloned genes in the vector pMD 18-T was confirmed by DNA sequencing (Invitrogen Biotech, Shanghai, China). Previous studies have shown the distribution of different virulence genes among V. cholerae, V. mimicus, V. alginolyticus and V. parahaemolyticus (Ghosh et al, 1997;Sechi et al, 2000;Shi et al, 1998;Shinoda and Nakagawa, 2004;Xie et al, 2005). Our results indicate that the virulence genes such as toxS, flaB and flaC are widely distributed among different vibrios, whereas zot and tcpA only exit in a few vibrios.…”
supporting
confidence: 51%
See 2 more Smart Citations
“…The plasmids were transformed into E. coli JM109 competent cells, and the sequence of the cloned genes in the vector pMD 18-T was confirmed by DNA sequencing (Invitrogen Biotech, Shanghai, China). Previous studies have shown the distribution of different virulence genes among V. cholerae, V. mimicus, V. alginolyticus and V. parahaemolyticus (Ghosh et al, 1997;Sechi et al, 2000;Shi et al, 1998;Shinoda and Nakagawa, 2004;Xie et al, 2005). Our results indicate that the virulence genes such as toxS, flaB and flaC are widely distributed among different vibrios, whereas zot and tcpA only exit in a few vibrios.…”
supporting
confidence: 51%
“…ebi.ac.uk/clustalw/), and the primers were designed from the homogenous region of the zot gene from V. mimicus (AY207857). For the amplification of the toxS gene, the primers described by Sechi et al (2000) were used. For the amplification of the tcpA gene, nucleotide sequences of V. cholerae O1 (AF536869), V. cholerae O1 (AF512414), V. mimicus (AF31578) and V. mimicus (DQ356010) were aligned, and the primers for PCR were designed from the homogenous region of the tcpA gene of V. mimicus (AF315787).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the genome contained homologs of many virulence genes that are commonly found in Vibrio species pathogenic to human and other animals. Wide distribution of virulence genes among coastal, estuarine, and riverine Vibrio species, including V. parahaemolyticus, V. cholerae non-O1, Vibrio mimicus, Vibrio hollisae, Vibrio fluvialis, and V. alginolyticus are well known (59)(60)(61); however, finding these virulence genes in a deep-sea Vibrio sp. raises a significant question whether pathogenicity genes, in addition to pathogenicity for humans and other animals, are in fact providing ecological functions in the natural environment.…”
Section: Discussionmentioning
confidence: 99%
“…Em casos raros, a infecção por V. parahaemolyticus pode ser fatal (7) . O gene ToxR está presente em todas as cepas de V. parahaemolyticus (9)(10)(11) , podendo ser encontrado em isolados patogênicos ou não patogênicos (12) . Este gene possui um fragmento de 368 pares de base (pdb) específico para Vibrio parahaemolyticus que é encontrado em todos os isolados (13) .…”
Section: Introductionunclassified